Effect of nutritional intervention combined with vitamin D on glucose metabolism, sex hormones and inflammatory factors in patients with Polycystic ovary syndrome: Impact of nutritional interventions on PCOS - Kang, Xinqin; Liu, Lin (Journal of Medical Biochemistry, 2025)
-